Iron Age settlement patterns at Salūt c.1300-300 BC - Condoluci, Chiara; Degli Esposti, Michele; Phillips, Carl (Proceedings of the Seminar for Arabian Studies, 2014)
The Wādī Bahla region of the Sultanate of Oman entered the record of the areas of archaeological relevance forty years ago, thanks to the work of the Harvard Archaeological Expedition. Among several Bronze Age sites, two Iron Age sites were identified and numbered BB15 and BB4. Site BB15, now widely known as ’Salūt’, was also visited shortly afterwards by Beatrice de Cardi. More recent excavations at the site, by the Italian Mission to Oman (IMTO) in cooperation with the Office of the Adviser to His Majesty the Sultan for Cultural Affairs, have provided the opportunity for a more detailed survey of Iron Age remains located nearby. The latter include areas of settlement, places of burial, and other possibly contemporary features. The surveys gave back a substantial surface collection of pottery, which has been extensively illustrated and can be compared with the pottery typology established by the excavations at Salut, which also easily finds parallels from other Iron Age sites in southeastern Arabia. New data allow a refinement of the chronological sequence of the area, while distribution maps resulting from this investigation, and consideration of the variety of sites, can be compared with similar data and Iron Age settlement patterns found elsewhere in south-east Arabia.